Choosing a career in the restaurant industry - Beal, Eileen (New York : Rosen Pub. Group, 1999)
Introduces various career opportunities in the restaurant industry, from wait staff to managers to owners.
Includes bibliographical references (p. 61-62) and index.
Keywords: Food service -- Vocational guidance -- Juvenile literature; Restaurants -- Vocational guidance; Food service -- Vocational guidance; Vocational guidance